Design and development of non-woven medical product from Wrightia tinctoria fiber. Issue 4 (19th May 2019) - Mothilal, B.; Prakash, C.; Ramakrishnan, G.
ABSTRACT: This work aims at research on characterization of Wrightia tinctoria fiber, such as fiber content, fiber longitudinal view, cross-sectional view, fiber diameter, moisture content, SEM analysis, surface resistivity, swelling, and also mechanical properties of fiber, such as fiber strength, elongation, linear density, etc. The fiber was used to produce carded webs using the pilot carding machine from blends of Wrightia tinctoria fiber (W) with cotton (C), bamboo (B), and polyester (P) in the blend ratios of 25:75 and 50:50 for required GSM. The produced webs were bonded using spunlace bonding technique to produce required non-woven medical apparel. The produced nonwoven were tested for dressing mass and thickness, absorbency of wound dressing, the dehydration rate of dressing, wettability, vertical wicking, air permeability, potential of hydrogen, water vapor permeability, and anti-bacterial. The test results of the studies were investigated in detail and observed that the product development from Wrightia tinctoria fiber has immense potential for curing various skin diseases as revealed from the test results.